Mathematical Computation of the Flow of Non-Newtonian Fluid with Heat Generation in a Cylindrical Pipe - Ibe, Akunna; Akpan, Anthony Udo; Anyaogu, Uche (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
In this paper, a mathematical computation of flow of non-Newtonian fluid with heat generation in a cylindrical pipe is undertaken and studied using the third-grade parameter to represent the non-Newtonian parameter. The coupled system of nonlinear ordinary differential equation (ODE) is solved using the traditional perturbation technique. The results show that the third-grade parameter (????) and the magnetic field parameter(M) reduces the flow velocity and the temperature while the Brinkman number enhances the temperature of the cylindrical walls. Some quantitative and numerical result are also presented to strengthen the utility of the method.